Rational Component and Structure Design of Noble‐Metal Composites for Optical and Catalytic Applications. Issue 4 (15th January 2021) - Zeng, Xiaojun; Zhao, Yang; Hu, Xudong; Stucky, Galen Dean; Moskovits, Martin
Abstract : Great effort has recently been made to develop noble‐metal nanomaterials with good activity, high durability, and appropriate selectivity to improve their efficiency in functional applications, while maintaining low cost. The use of noble metals not only makes the last requirement hard to meet but also restricts stability at high temperatures and limits mass production. Recently, some promising strategies, such as optimizing the components and fine‐tuning the structure, have been explored, which promise to enable the fabrication of unique noble‐metal nanostructures with lower loading and higher stability. Herein, recent achievements in manufacturing noble‐metal composites are reviewed, particularly focusing on unique and key factors in rational design and control of structure and components. Two applications of noble‐metal composites in optical and catalytic applications are focused on to illustrate their rational synthesis and design. In addition, current challenges and prospects for future development in this rapidly blossoming field are discussed. Abstract : The high cost and scarcity of noble‐metal nanomaterials have motivated researchers to develop novel strategies, some based on uniquely designed, novel nanostructures, thereby improving the range of their utility and stability in functional applications. Herein, recent achievements in the synthesis strategy and structural design of noble‐metal composites and their applications in optics and catalysis are systematically highlighted.